Development of a simulation-based learning model for building information modeling course in vocational civil engineering education - Ari Syaiful Rahman Arifin; Faisal Ashar; Risma Apdeni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
The rapid adoption of Building Information Modeling (BIM) in the construction industry requires vocational civil engineering graduates to develop competencies beyond technical modeling skills, including interdisciplinary coordination and collaborative project workflows. However, BIM instruction in vocational higher education remains predominantly software-oriented and lacks structured integration of authentic industry practices within formal coursework. This study aimed to develop and validate a semester-integrated simulation-based learning model embedded in a compulsory BIM course. Using a Research and Development approach based on the ADDIE framework, the study involved competency gap analysis, model design, expert validation, and classroom implementation. Five experts—two BIM academics, one instructional design specialist, and two industry practitioners—evaluated the model, resulting in an overall mean feasibility score of 4.48 (SD = 0.18), categorized as Highly Valid. The model was implemented over one semester with 32 fourth-semester students. CLO-aligned performance assessment showed average scores of 82.6 in modeling accuracy, 79.4 in coordination quality, 84.1 in clash detection effectiveness, and 86.3 in teamwork, while 81% of students reported improved understanding of interdisciplinary BIM workflows. The findings demonstrate that structured simulation supports industry-aligned competency development in vocational BIM education.